The Other Side of the History of the Formulation of Aceh Jinayat Qanun - Salma Salma; Almuh Fajri; Taufik Hidayat; Edi Safri (AHKAM : Jurnal Ilmu Syariah, 2022)
In the context of fiqh, the provisions of ḥudūd have been agreeable in terms of the actions and punishments. However, some of them are not mentioned in Aceh Qanun No. 6/2014 on Jinayat (Criminal) Law, such as stoning, death sentence, and hand amputation. These three types of punishment were harshly debated during the formulation of the qanun and subsequently abolished. Using the historical legal approach, this study finds out there were some issues that came up during the formulation process. First, the assessment of the local government and people’s readiness to implement those punishments has not been sufficient. Second, stoning, the death penalty, and hand cutting are not in accordance with the Indonesian procedural law. Third, the qanun formulation was affected by the disparity of Islamic legal scholars’ opinions regarding the mentioned penalties. Forth, the discussants in the forum believed that the implementation of Islamic criminal law needs phasing (tadarruj).   AbstrakDalam konteks fikih, ketentuan hudud telah disepakati baik jenis perbuatannya maupun sanksi-sanksinya. Akan tetapi, tidak semuanya tercantum sebagai materi hudud dalam Qanun Aceh No. 6/2014 tentang Hukum Jinayat, seperti hukuman rajam, hukuman mati dan hukuman potong tangan. Ketiga jenis hukuman ini diperdebatkan dengan sengit selama pembahasan Qanun dan akhirnya ditiadakan. Melalui pendekatan sejarah hukum, diketahui setidaknya ada beberapa faktor problematik yang mewarnai perumusan Qanun Aceh No. 6/2014 tentang Hukum Jinayat. Pertama, adanya penilaian internal tentang kesiapan pemerintah dan masyarakat yang belum maksimal untuk melaksanakan hukuman-hukuman itu. Kedua, materi rajam, hukuman mati bagi pelaku riddah dan potong tangan yang tidak sejalan dengan hukum acara yang telah ada sebelumnya. Ketiga, adanya pengaruh perbedaan pendapat ulama (disparitas) dalam konteks fikih tentang hukuman-hukuman itu dalam proses perumusan qanun. Keempat, adanya keyakinan para pembahas bahwa penegakan hukum pidana Islam dalam Qanun Aceh memerlukan pentahapan (tadarruj).